Overeducation and mismatch in the labor market - Edwin Leuven; Hessel Oosterbeek (Institute for the Study of Labor (IZA), 2011)
This paper surveys the economics literature on overeducation. The original motivation to study this topic were reports that the strong increase in the number of college graduates in the early 1970s in the US led to a decrease in the returns to college education. We argue that Duncan and Hoffman's augmented wage equation the workhorse model in the overeducation literature in which wages are regressed on years of overschooling, years of required schooling and years of underschooling is at best loosely related to this original motivation. We discuss measurement and estimation issues and give an overview of the main empirical findings in this literature. Finally we given an appraisal of the economic lessons learned.
urn:nbn:de:101:1-201104113963
Keywords: I2; 330; mismatch; overschooling; underschooling; wage equation; Unterbeschäftigung; Lohn; Bildungsertrag; Akademiker; Schätzung; USA